A storymap: Japanese occupation in Malaya digital storytelling - Ahmad Pugi, Noorsazwan; Mohamad, Azlizan Adila; Che Hashim, Izrahayu; Hashim, Haslina; Nasron, Nursyahani (Universiti Teknologi MARA, Kedah, 2023)
The Japanese Occupation brought significant socio-political, economic, and cultural changes in Malayan society, and its impact continues to resonate today. It began when the 25th Japanese Army invaded Malaya on December 8, 1941. The Japanese army launched an amphibious assault on the northern coast of Malaya in Kota Bharu and began to advance down to the eastern coast of Malaya. The importance to gain a deeper understanding of this historical period is proved as it is used as oneof the topics in History subject for secondary school. However, traditional approaches to learning history, such as textbooks, often fail to fully capture the complexity and depth of this period, hindering audience engagement and understanding. Therefore, this project aims to provide a comprehensive and immersive exploration of the Japanese Occupation in Malaya using a web-based interactive story map platform, ArcGIS StoryMaps. By integrating interactive maps, visuals, primary sources, and narratives, it provides insight into the historical significance, and the enduring consequences of the occupation. The objectives of this research are to create a chronology narrative topresent the key events of the Japanese Occupation in Malaya and to provide geospatial context by integrating maps and visualizing the movement of forces and events. The methodology involves gathering historical data, photographs and sources related to the occupation. This data is then utilized to develop a cohesive narrative and storyboard for the story map. Through the integration of interactive maps and multimedia elements, it allows users to explore the spatial and temporal dimensions of the occupation, actively engage with the learning material and gain a deeper understanding of this important period in the history of Malaya.